Authoritative Teaching Practices in the Implementation of the Independent Curriculum in Indonesia: A Student-Centered Survey Analysis: Penelitian - Andi Sahtiani Jahrir; Asiz Nojeng (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Independent Curriculum emphasizes student autonomy, contextual learning, and teacher flexibility. Within this framework, teachers act as facilitators whose approaches influence student engagement and character. This study examines teacher parenting styles—authoritative, authoritarian, and permissive—in the implementation of the Independent Curriculum, based on the perceptions of elementary and junior high school students in Makassar. The study used a quantitative survey method with 257 students from 17 public and private schools through questionnaires assessing teacher-student interactions, discipline strategies, emotional responses, and classroom decision-making. Descriptive analysis revealed the authoritative style as the most dominant, characterized by emotional support, clear expectations, and student motivation. However, aspects of authoritarian and permissive styles also emerged, particularly in inconsistent rules and a lack of responsiveness to student aspirations. This variation is influenced by contextual factors and differences in teacher professional development. Effective implementation of the Independent Curriculum requires consistent authoritative practices. These findings emphasize the importance of teacher training in emotional regulation, inclusive pedagogy, and formative discipline, and encourage national education policies to strengthen character-based learning and teacher-student relationships in line with 21st-century competencies.